Bivalirudin Anticoagulation for Cardiopulmonary Bypass: An Unusual Case - Nikolaidis, Nicolas (2007)
The standard agent used for systemic anticoagulation during cardiopulmonary bypass is heparin. Alternative methods of anticoagulation are required for patients with heparin hypersensitivity. We present the case of a patient with heparin hypersensitivity who was anticoagulated with bivalirudin during cardiopulmonary bypass for coronary artery bypass grafting. This presented unusual challenges surrounding the monitoring of anticoagulation and the method of myocardial protection.